2012
DOI: 10.1093/pcp/pcs046
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis P-Protein Filament Formation Requires Both AtSEOR1 and AtSEOR2

Abstract: The structure-function relationship of proteinaceous filaments in sieve elements has long been a source of investigation in order to understand their role in the biology of the phloem. Two phloem filament proteins AtSEOR1 (At3g01680.1) and AtSEOR2 (At3g01670.1) in Arabidopsis have been identified that are required for filament formation. Immunolocalization experiments using a phloem filament-specific monoclonal antibody in the respective T-DNA insertion mutants provided an initial indication that both proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 41 publications
8
78
0
Order By: Relevance
“…However, the formation of heteromers could not be demonstrated for AtSEO proteins. 11 A potential explanation for the successful demonstration of SEO heteromer formation in this study might be the plant background. To examine whether this is the case or if the differing observations are species-specific, BiFC experiments should be performed with than corresponding wild-type plants upon injury, confirming the ability of P-proteins to seal the phloem, although additional functions are certainly conceivable.…”
Section: Seo Genes Encode Structural Phloem Proteins In Angiospermsmentioning
confidence: 82%
See 2 more Smart Citations
“…However, the formation of heteromers could not be demonstrated for AtSEO proteins. 11 A potential explanation for the successful demonstration of SEO heteromer formation in this study might be the plant background. To examine whether this is the case or if the differing observations are species-specific, BiFC experiments should be performed with than corresponding wild-type plants upon injury, confirming the ability of P-proteins to seal the phloem, although additional functions are certainly conceivable.…”
Section: Seo Genes Encode Structural Phloem Proteins In Angiospermsmentioning
confidence: 82%
“…This was recently addressed in a study dealing with the Arabidopsis thaliana SEO genes At3g01670 and At3g01680. 11 We recommend that the original names (AtSEOR1 and AtSEOR2, for sieve element occlusion related) are replaced with AtSEOa (At3g01670) and AtSEOb (At3g01680) as we proposed earlier, 4 because their direct role in sieve tube sealing is now acknowledged. 7 The analysis of T-DNA insertion mutants and corresponding complementation lines strongly indicated that interactions between AtSEOa and AtSEOb are necessary to form phloem filaments as no P-protein structures could be observed when either AtSEOa or AtSEOb was knocked out.…”
Section: Ntseo1 and Ntseo2 Form Heteromeric Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A fusion between the splitmRFP variants to the monomeric Emerald protein (mEmerald) was used as a control. [7][8][9][11][12][13] All BIFC constructs were introduced into Agrobacterium tumefaciens strain GV3101 pMP90 by electroporation and the resulting bacteria were infiltrated into 4-wk-old N. benthamiana plants. A. tumefaciens strain C58C1 (carrying the pCH32 helper plasmid) was co-infiltrated to inhibit gene silencing.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 The group 1 SEO proteins are only present in papilionoid legumes and these represent forisome subunits, whereas members of groups 5 and 6 represent the common P-proteins in most dicot species that probably cause irreversible sieve element occlusion. [5][6][7][8] In our recent study, we expressed group 1 SEO-F genes from different legumes in a heterologous background to study their impact on forisome assembly, including the DpSEO-F1 gene from the basal papilionoid species D. panamensis. 9 The D. panamensis lineage diverged from lineages of the Old World clade, i.e., Canavalia gladiata, Lotus japonicus, and Medicago truncatula, more than 50 million years ago.…”
mentioning
confidence: 99%